Systematic review of the effect of probiotics on experimental gingivitis in humans - Eliane Porto Barboza; Patricia Carvalho Arriaga; Diogo Pereira Luz; Caroline Montez; Katia Costa Vianna (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract: Probiotic therapy is a viable alternative to chlorhexidine, a widely used antiseptic in dentistry that produces significant adverse effects. This systematic review aimed to analyze the effects of probiotics on experimental gingivitis in humans. Two independent reviewers conducted a comprehensive literature search until March 2019. Randomized clinical trials and controlled clinical trials were selected. Outcome data were extracted and critically analyzed. A total of five articles were included in the qualitative synthesis. No meta-analysis could be conducted due to the heterogeneity of the selected studies. The use of probiotics showed a slight improvement in clinical parameters. Changes in gingival crevicular fluid volume were lower in the presence of the probiotic than in the placebo group. All the studies showed that the immediate, positive effects of probiotics during the period of discontinued mechanical oral hygiene were due to the modulation of the host response, not the anti-plaque effect. Investigators should conduct randomized clinical trials to elucidate the mechanisms of probiotic action and develop improved delivery systems.